Multifunctional Characteristics of Glass Fiber-Reinforced Epoxy Polymer Composites with Multiwalled Carbon Nanotube Buckypaper Interlayer - Ribeiro, Bruno; Corredor, Jefersson Alexander Rojas; Costa, Michelle Leali [UNESP]; Botelho, Edson Cocchieri [UNESP]; Rezende, Mirabel Cerqueira (Wiley, 2020)
In this work, multiwalled carbon nanotube buckypaper (MWCNT-BP) was inserted at the middle-plane of glass fiber/epoxy resin prepregs to obtain three-phase nanostructured composite. Preliminary tests conducted by differential scanning calorimetry and thermogravimetric analyses (TGA) revealed that the proposed curing cycle to prepare the laminates in a hot compression-molding machine was appropriated. The mechanical properties of the BP-based composite studied by short beam shear and compression shear tests presented no improvements compared to the base laminate. On the other hand, the thermal properties of the nanostructured composite improved as demonstrated by dynamical mechanical analyses and TGA. Besides, the reflectivity results revealed an average value of −12.2 dB in the X-band with a maximum attenuation of 99.4% of the incident wave at 9.5 GHz. The improvements in both thermal and electromagnetic properties demonstrate the potential for both structural and multifunctional applications of the obtained BP-composite. POLYM. ENG. SCI., 60:740–751, 2020. © 2020 Society of Plastics Engineers.